Ultrasonographic diagnosis and minimally invasive treatment of a patent urachus associated with a patent omphalomesenteric duct in a newborn: A case report. Issue 30 (July 2017) - Bertozzi, Mirko; Recchia, Nicola; Di Cara, Giuseppe; Riccioni, Sara; Rinaldi, Victoria Elisa; Esposito, Susanna; Appignani, Antonino
Abstract: Rational: Patent urachus (PU) is due to an incomplete obliteration of the urachus, whereas patent omphalomesenteric duct (POMD) is due to an incomplete obliteration of the vitelline duct. These anomalies are very rarely associated with one another. We describe a case of a newborn with a PU associated with a POMD, who was diagnosed by an abdominal ultrasound (US) and laparoscopy, and managed with a minimally invasive excision. Patient concern: A 28-day-old male neonate was referred to our hospital to investigate a delay in umbilical healing, with blood-mucinous material spillage for 3 weeks prior to the referral. The baby had no symptoms and was in good general health. Diagnosis: After a thorough cleaning of the umbilical stump, a clear granuloma with a suspected fistula was evident under the seat of the ligature of the stump. An abdominal US examination revealed the formation of a full communication, starting below the umbilical stump and developing along the anterior abdominal wall that connected with the bladder dome. The US also revealed a tubular formation containing air, which was compatible with POMD, in the deepest portion of the same umbilical stump. Considering these findings, the rare diagnosis of a PU associated with a POMD duct was suspected. Interventions: The child was then hospitalized for an elective laparoscopy that confirmed the US picture, and a minimally invasive excision was performed. Outcome: The postoperative course was favorable and uneventful. Lessons: Our case underlines the importance of evaluating all persisting umbilical lesions without delay when conventional pharmacological therapies fail. Using a US as the first approach is valuable and should be supported by laparoscopy to confirm the diagnosis; a minimally invasive excision of the remnants appears to be an effective therapeutic approach.